2011
DOI: 10.17221/1437-cjas
|View full text |Cite
|
Sign up to set email alerts
|

Intra-line and inter-line genetic diversity in sire lines of the Old Kladruber horse based on microsatellite analysis of DNA

Abstract: ABSTRACT:The Old Kladruber horse is the oldest original Czech horse breed -gene resource, with pedigree records spanning three centuries. Because the population is closed, there is a concern about the loss of genetic variation. The genetic diversity within and amongst sire lines was evaluated using microsatellite markers and based on pedigree information. The DNA analysis, covering 16 microsatellite loci, revealed that the genetic diversity (observed heterozygosity = 0.637, genetic diversity = 0.678 and the me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
3
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 23 publications
(26 reference statements)
5
3
0
Order By: Relevance
“…These results were in agreement with the conclusions published by Vostrý et al (2011a). Vostrý et al (2011a) showed that disparity between sire lines was not from obvious genetic factors.…”
Section: Choice Of a Suitable Modelsupporting
confidence: 93%
See 1 more Smart Citation
“…These results were in agreement with the conclusions published by Vostrý et al (2011a). Vostrý et al (2011a) showed that disparity between sire lines was not from obvious genetic factors.…”
Section: Choice Of a Suitable Modelsupporting
confidence: 93%
“…These results were in agreement with the conclusions published by Vostrý et al (2011a). Vostrý et al (2011a) showed that disparity between sire lines was not from obvious genetic factors. The inclusion of the fixed effect of year of description (Model 3) versus the fixed effect of year of birth (Model 2) resulted in a decrease in the value of σ 2 e for the 22 linear type descriptions of conformation and type characters.…”
Section: Choice Of a Suitable Modelsupporting
confidence: 93%
“…Estimated parameters of genetic diversity exhibited non-significant differences between breeds (Table 2), which fully corresponds to their historical development. Genetic diversities within the studied breeds reached similar values to those in the Old Kladruber horse (Vostry et al 2011;Kasarda et al 2016), the breed that also belongs to genetic resources of the Czech Republic. The determined values of genetic diversity were lower than e.g., those in Polish cold-blood horses (Iwanczyk et al 2006) or Polish Konik (Szwaczkowski et al 2016).…”
Section: Discussionsupporting
confidence: 62%
“…To maintain the great variability and optimal body composition, the linear description of type can be useful for stabilization and corrective mating in particular cases. Vostrý et al (2011a) found average values of the inbreeding coefficient (F X ) to be 7.3% in the Old Kladruber horse. Similar results were published by Vostrý et al (2011b) on Czech cold-blooded breeds of horses.…”
Section: Breeding Valuesmentioning
confidence: 99%